Pelatihan Penggunaan Instagram dalam Promosi Produk Kuliner - Ira Brunchilda Hubner,; Juliana,; Rudy Pramono,; Sandra Maleachi,; Deandra Asthyn Pakasi,; Nova Bernedetta Sitorus, (TAAWUN, 2021)
The role of social media is very important for the advancement of various fields in this digital era. The existence of a pandemic and the rules that have been set, such as restrictions on the application of community activities have made many small and medium businesses, especially culinary products, have to sell their products online. The Faculty of Tourism of Pelita Harapan University has invited partners of Culinary Department SMKN7 to carry out Community Service (PkM) through a webinar entitled Training on the Use of Social Media in Promotion of Culinary Products. This PkM provides training to students of the Catering Department to be able to sell culinary products that are produced to be easily accepted by the community by utilizing the role of social media. This PkM is expected to be a lesson to broaden your horizons on how to use promotional strategies by maximizing the use of social media roles in promoting culinary products you want to sell. The method used is to conduct webinars with the zoom application. This webinar provides the results of a better understanding of the participants to increase creativity in developing strategies for compiling the content of the culinary products produced so that they are more accessible to the public.